Psychological predictors of emotional divorce in couples - Parvaz, Younes; Salek Ebrahimi , Leila; Mousavi, Seyedeh Elnaz (Researcher Bulletin of Medical Sciences, 2022)
Objective: Emotional divorce in today’s society is a silent problem and leads to marital dissatisfaction, so the purpose of this study is to investigate the psychological predictors of emotional divorce in couples. Method: This research was descriptive-analytical. The study population was all couples in Zanjan city. The sample size according to Free Statistics Calculators Version4 was 423 people. Using random cluster sampling, married people from Zanjan were randomly selected. Guttmann Emotional Divorce, Internet Addiction, and Humor styles Questionnaires were randomly assigned to participants to complete. Finally, for the final analysis of the data, including 413 descriptive statistics and structural models were performed. In order to investigate the structural model due to the normality of the data and the acceptability of other prerequisites, as well as the graphical environment and high capability of AMOS software, version 22 of this software package was used. Results: In the final general model, 35% of the variance of emotional divorce was explained by the variables of sexual satisfaction and Internet addiction, and the fit indices were appropriate and acceptable. The data showed that sexual satisfaction (64) was more important for men in emotional divorce. Among women, Internet addiction had more explanatory power in emotional divorce than sexual satisfaction. The Internet addiction pathway coefficient was about 66. and the sexual satisfaction pathway coefficient was about 48. Conclusion: Emotional divorce is a multi-factor or multi-causal phenomenon that is affected by both psychological and sociological factors. As shown in the findings section, Internet addiction and sexual satisfaction were strongly predictors of emotional divorce